Ensuring Fiscal Sustainability in Japan in the Context of a Shrinking and Ageing Population - Jones, Randall S.. (OECD Publishing, 2017)
With gross government debt of 219% of GDP in 2016, Japan's fiscal situation is in uncharted territory and puts the economy at risk. In addition to raising productivity and growth, Japan needs a more detailed and credible fiscal consolidation path, including specific revenue increases and measures to control spending to restore fiscal sustainability. Spending pressures associated with rapid population ageing make reforms to contain social expenditures a priority. Local governments need to be part of the effort to contain public spending in the context of a shrinking population. Much of the consolidation, though, will have to be on the revenue side, primarily through hikes in the consumption tax rate toward the OECD average and a broadening of the personal income tax base. Fiscal consolidation should be accompanied by measures to promote inclusive growth through the tax and benefit system, in particular by introducing an earned income tax credit to assist the working poor, hiking the tax on capital income and broadening the base of the inheritance tax. This Working Paper relates to the 2017 OECD Economic Survey of Japan (www.oecd.org/eco/surveys/economic-survey-japan.htm)
Keywords: Economics; Japan